2022
DOI: 10.3389/fimmu.2022.960738
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of prognosis, immunogenicity and efficacy of immunotherapy based on glutamine metabolism in lung adenocarcinoma

Abstract: BackgroundGlutamine (Gln) metabolism has been reported to play an essential role in cancer. However, a comprehensive analysis of its role in lung adenocarcinoma is still unavailable. This study established a novel system of quantification of Gln metabolism to predict the prognosis and immunotherapy efficacy in lung cancer. Further, the Gln metabolism in tumor microenvironment (TME) was characterized and the Gln metabolism-related genes were identified for targeted therapy.MethodsWe comprehensively evaluated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…The prognostic markers and the indications for prognosis in these studies are summarized in Table 2 . 36 , 44 , 45 , 47 49 , 55 89 DEGs and their combined prognostic model were the most common types of prognostic markers in these studies. For example, one study identified nine cancer-specific DEGs (CBFA2T3, CR2, SEL1L3, TM6SF1, TSPAN32, ITGA6, MAPK11, RASA3, and TLR6) and established a prognostic risk model in combination with clinical factors.…”
Section: The Prognostic Time Markers For Luadmentioning
confidence: 91%
See 1 more Smart Citation
“…The prognostic markers and the indications for prognosis in these studies are summarized in Table 2 . 36 , 44 , 45 , 47 49 , 55 89 DEGs and their combined prognostic model were the most common types of prognostic markers in these studies. For example, one study identified nine cancer-specific DEGs (CBFA2T3, CR2, SEL1L3, TM6SF1, TSPAN32, ITGA6, MAPK11, RASA3, and TLR6) and established a prognostic risk model in combination with clinical factors.…”
Section: The Prognostic Time Markers For Luadmentioning
confidence: 91%
“…The studies on therapeutic response and details of the markers are summarized in Table 3 . 40 , 44 , 57 , 61 , 64 , 69 , 75 , 76 , 78 , 81 , 82 , 86 , 88 , 89 , 91 99 Several DEGs have been found to predict patient response. In one study, four immune-related genes, including PTPRC, CCR2, SLAMF1, and HLA-DQA2 were identified as the signature for better outcomes.…”
Section: The Time Markers For Luad Therapeutic Responsementioning
confidence: 99%
“… 194 The researchers discovered that the tumor‐infiltrating T cells (especially CD8 T cell exhaustion and Treg suppression) presented the highest active levels of Gln metabolism among immune cells by building a quantitative system of Gln metabolism, which can be used to predict the prognosis and the immunotherapy efficacy including ICI and T cell adoptive therapy in lung cancer. 195 …”
Section: Relationships Between Immune Cell Metabolism Epigenetics Mod...mentioning
confidence: 99%
“…Tex amino acid metabolism is generally impaired, but glutamine metabolism is more highly active than it is at other stages of the CD8+ TIL transition process. 88 Notably, the significant upregulation of glutamine metabolism, associated with the activation of the transforming growth factor‐β (TGF‐β) signalling pathway, leads to a reduction in the expression of the tissue‐resident marker CD103 on Texs and induces T‐cell apoptosis and impairment. 89 Nevertheless, in the colorectal cancer microenvironment, glutamine not only enhances CD8+ T‐cell glycolysis and lactate metabolism but also serves as an essential nutrient for cytokine synthesis.…”
Section: T‐cell Metabolic Reprogramming and Related Antitumour Immune...mentioning
confidence: 99%